Gambaran Pemberian Hidroterapi Air Hangat dan Eco Enzyme Terhadap Nilai Tekanan Darah - Gultom, Venny Mayumi; Darmansyah, Ari (JURNAL KESEHATAN TERAPAN, 2024)
Blood pressure is a crucial element in the functioning of the body's circulatory system. Blood pressure fluctuations, both rising and falling, potentially affect the internal balance of the body. Hypertension can cause damage to blood vessels and vital organs such as the heart, kidneys, and brain. By contrast, low blood pressure (hypotension) can cause dizziness, fatigue, and in severe cases, even fainting or shock. One of the non-pharmacological ways to lower blood pressure is to use hydrotherapy, like sinking the legs. The aim of this study is to identify differences in blood pressure before and after foot immersion therapy using warm water and eco enzymes. The design of this study is a pre-experiment one group pretest-postest. The population of this study was the entire population in the area of the study, with sampling done using purposive samplings with the inclusion criteria of ages 20-60 years old, physically healthy, and without an injury to the ankle. The exclusion criteria included pregnant women and subjects who were unwilling to participate as respondents, which is as many as 30 people as samples. Foot immersion therapy is performed using warm water mixed with eco enzymes, with temperature conditions ranging from 38°C to 40°C, for 30 minutes. The results of this study showed that there was a difference between the systolic and diastolic blood pressure values before and after the administration of foot immersion therapy with eco enzymes. The results suggest that people with hypertension can do their own foot immersion therapy at home as a preventive effort to control the rise in blood pressure and reduce the risk of complications, thereby improving their quality of life.